2021
DOI: 10.1177/1074840720975869
|View full text |Cite
|
Sign up to set email alerts
|

Parental Decision-Making in the Pediatric Intensive Care Unit: An Integrative Review

Abstract: Parents are commonly responsible for making health care decisions for their seriously ill children in the pediatric intensive care unit (PICU); however, the factors influencing their decisions may vary. This integrative review examined the empirical literature between 2013 and 2018 to understand factors pertaining to parents’ decision-making about serious illness care of their children in the PICU. Seventeen studies met the inclusion criteria with three key findings. First, parent–clinician communication in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(110 reference statements)
1
3
0
Order By: Relevance
“… 3 Our review found that end-of-life decisions affected parents emotionally, causing guilt and regret, even though they were not responsible for the final decision. These feelings of guilt have previously been reported 16 , 17 in relation to parents’ reflections on the role they were expected to play for their infants. 18 Feelings of guilt and regret have also been reported to effect parents’ decision-making and their ability to cope with the consequences.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“… 3 Our review found that end-of-life decisions affected parents emotionally, causing guilt and regret, even though they were not responsible for the final decision. These feelings of guilt have previously been reported 16 , 17 in relation to parents’ reflections on the role they were expected to play for their infants. 18 Feelings of guilt and regret have also been reported to effect parents’ decision-making and their ability to cope with the consequences.…”
Section: Discussionsupporting
confidence: 58%
“… 18 Feelings of guilt and regret have also been reported to effect parents’ decision-making and their ability to cope with the consequences. 17 When parents make decisions for their infant, they have to balance the best interests of their infant and their own emotional burden. 3 Thus, inappropriate moral responsibility can be avoided by acknowledging the parents’ willingness to take responsibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in conflict with the fundamental values of family-centered care, where families should be considered as true partners in care of their child and fully empowered to be able to make informed decisions ( 28 , 37 ). To achieve this, parents' individual needs of information and communication need to be considered ( 38 ), parents should be allowed to participate in their child's care as desired ( 39 ), and be informed and invited to participate in shared decision-making ( 40 ). Our study also highlight what caused the loss of a trusting relationship between participants and HCPs, and what facilitated it.…”
Section: Discussionmentioning
confidence: 99%